THE USE OF GROUP DISCUSSION METHOD TO IMPROVE STUDENTS’ SPEAKING ABILITY AT THE TENTH GRADE OF SMA NEGERI 1 LOLOWAU - Damari Laia (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2026)
Speaking is one of the important language skills. However, many students at SMA Negeri 1 Lolowau got weaknesses in speaking. So, this research aimed at improving students' speaking skills through the Group Discussion method. This research was designed using the classroom action research (CAR) method. The research subject was class X MIPA 1 which consisted of 22 students. The instruments of data collection were observation paper and test. Based on data analysis, the results of the researcher's observations in cycle I at the first meeting was 77% and at the second meeting was 85%. In cycle II, the first meeting was 85% and the second meeting was 92%. Meanwhile, the result of student observation in cycle I of the first meeting was 62% and the second meeting was 75%. Then in cycle II the first meeting was 83% and the second meeting was 88%. Furthermore, the student test results in cycle I showed that 9 students passed or 41% and 13 students failed or 59% with an average score of 57. Then the test results in cycle II experienced an increase where 19 students passed or 86% and 3 people or 14% failed with an average score of 71. Based on these findings, it can be concluded that the Group Discussion method is the right method to apply in teaching speaking. It is suggested for English teachers to apply the Group Discussion method in teaching speaking because this method can improve students’ speaking ability.